Text summarization in android mobile devices - Foong, O.-M. (Springer Verlag, 2014)
This paper presents a text summarization in Android mobile devices. With the proliferation of small screen devices and advancement of mobile technology, the text summarization research has been inspired by the new paradigm shift in accessing information ubiquitously at anytime, anywhere and anyway on mobile devices. However, it is a challenge to browse large documents in a mobile device because of its small screen size and information overload problems. In this paper, a semantic and syntactic based summarization was attempted and implemented in a text summarizer. The objectives of the paper are two-fold. (1) To integrate WordNet 3.1 into the proposed system called TextSumIt which condenses single lengthy document into shorter summarized text. (2) To provide better readability to Android mobile users by displaying the salient ideas in bullets points. Documents were collected from DUC 2002 and Reuter news datasets. Experimental results show that the text summarization model improves the accuracy, readability and time saving in the text summarizer as compared with MS Word AutoSummarize. Â© Springer Science+Business Media Singapore 2014.